From Patronage to Programmatic Governance: PKB’s Institutional Adaptation Strategy in East Java - Ramdlani, Muhammad Farih; Hamid, Achmad Zainulloh; Munhanif, Ali (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2026)
This study analyzes the electoral resilience of the National Awakening Party (PKB) in East Java following the implementation of the equidistance policy by the Executive Board of Nahdlatul Ulama (PBNU) in 2021. Designed to decouple the religious organization from practical politics, this policy precipitated patronage disarticulation, effectively severing the traditional mobilization channels linking NU and PKB. Employing a qualitative case study approach based on in-depth interviews and document analysis, this research investigates how PKB sustained its vote share in the 2024 Legislative Election despite the withdrawal of structural support. The study identifies two primary survival strategies. First, the party adopted an institutional bypass strategy, leveraging informal networks of non-structural clerics and autonomous bodies (Banom) to circumvent formal organizational blockades. Second, PKB transitioned toward programmatic governance, exemplified by the legislative enactment of the Regional Regulation on Islamic Boarding Schools (Perda Pesantren). This maneuver established fiscal patronage, thereby securing constituent loyalty through state budgetary allocation rather than traditional religious deference. The study concludes that this organizational conflict catalyzed a critical shift from genetic dependence to forced autonomy, marking PKB's evolution into a policy-oriented political entity.